Linking the Timing of Deposition and Organic Matter Richness of the Gulneri Formation of Northern Iraq to the Global Oceanic Anoxic Event 2 (OAE 2): Implications to better constrain the Depositional Models of Iraqi’s Oil Source Beds and their Timing of De - Anazan Al-Sagri, Khedar Ezbar (Iraqi Journal of Science, 2023)
Global oceanic anoxic events (OAEs) are events of immense importance for a variety of reasons. For instance, they are not only behind most if not all of the mass extinctions which took place during the Cenozoic era, but they are the harbinger for the world’s best oil source beds, which humanity depends on to satisfy its energy need. In spite of this, there was little effort to document their presence in Iraq, to fill in for the void here, and as a first step, this paper will attempt to establish a cause and effect relationship between OAE 2 and the Gulneri Formation timing of deposition and organic matter richness. This was done by showing the prevalent occurrence of the globally known OAE 2 positive ∂13Corg excursion and the unique rock-eval fingerprints all through the Gulneri Formation.The lessons learned are rather many and important. First is the laying down of stringent constraints on the Gulneri Shale age assignment. In view of this study results, this formation age ought to be bracketed between the latest Cenomanian to the earliest Turonian, or in the language number between 93.5 to 93.9 Ma. The second lesson is the gaining of an in-depth expose about the depositional model responsible for making the Gulneri shale to become so rich in organic matter. It is hoped from all of this is to lay down a solid ground for constraining the depositional models of other Iraqi oil source beds.